2009
DOI: 10.1017/s1014233909990368
|View full text |Cite
|
Sign up to set email alerts
|

Estudio demográfico de los atributos morfológicos y productivos en poblaciones de llamas (Lama glama) de la provincia de Jujuy, Argentina

Abstract: Estudio demográfico de los atributos morfológicos y productivos en poblaciones de llamas (Lama glama) de la provincia de Jujuy, Argentina Resumen La población de llamas (Lama glama) del altiplano argentino y sur boliviano reúne características especiales en relación al resto de la especie. Si bien se ha establecido el interés de esta población como recurso genético no se han realizado muchos trabajos que describan sus características productivas. En este trabajo se establecieron relaciones entre edad, sexo, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
1
8
0
1
Order By: Relevance
“…A survey indicated that black, white and grey fibre fetch best prices (PROSAP, 2010). More than 80 percent of the Argentinian llama fibre is finer than 24 µm (Hick et al, 2009), which is equivalent to the Peruvian "superfine" (21-24 µm) class of commercial alpaca fibre. In comparison only 10 percent of Huacaya alpacas of Australian herds have fibre diameter below 24 µm (McGregor, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A survey indicated that black, white and grey fibre fetch best prices (PROSAP, 2010). More than 80 percent of the Argentinian llama fibre is finer than 24 µm (Hick et al, 2009), which is equivalent to the Peruvian "superfine" (21-24 µm) class of commercial alpaca fibre. In comparison only 10 percent of Huacaya alpacas of Australian herds have fibre diameter below 24 µm (McGregor, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Fleeces in-between SC and L are defined as hemiluster and fleeces in-between SC and DC are defined as intermediates. Following this definitions, Hick et al Furthermore, the results of Hick et al (2009) andFrank et al (2006a) indicate that according to the coat colour 41 percent of llamas were white, 27 percent were brown or tan coloured and 16 percent chestnut coloured. Only 16 percent were of other colours such as black, grey or mixed.…”
Section: Fibre Characteristics Of Llamasmentioning
confidence: 98%
See 2 more Smart Citations
“…(Hick et al . ). Compared with the guanaco, which has short fibers of 1.4–3.8 cm (Von Thüngen et al .…”
mentioning
confidence: 97%